Study of the Development of the Mouse Thoracic Aorta Three-Dimensional Macromolecular Structure using Two-Photon Microscopy. (January 2015) - Zadrozny, Leah M.; Neufeld, Edward B.; Lucotte, Bertrand M.; Connelly, Patricia S.; Yu, Zu-Xi; Dao, Lam; Hsu, Li-Yueh; Balaban, Robert S.
Using the intrinsic optical properties of collagen and elastin, two-photon microscopy was applied to evaluate the three-dimensional (3D) macromolecular structural development of the mouse thoracic aorta from birth to 60 days old. Baseline development was established in the Scavenger Receptor Class B Type I-Deficient, Hypomorphic Apolipoprotein ER61 (SR-BI KO/ApoeR61 h/h ) mouse in preparation for modeling atherosclerosis. Precise dissection enabled direct observation of the artery wall in situ. En-face, optical sectioning of the aorta provided a novel assessment of the macromolecular structural development. During aortic development, the undulating lamellar elastin layers compressed consistent with the increases in mean aortic pressure with age. In parallel, a net increase in overall wall thickness ( p <0.05, in day 60 compared with day 1 mice) occurred with age whereas the ratio of the tunicas adventitia and media to full aortic thickness remained nearly constant across age groups (~1:2.6, respectively). Histochemical analyses by brightfield microscopy and ultrastructure validated structural proteins and lipid deposition findings derived from two-photon microscopy. Development was associated with decreased decorin but not biglycan proteoglycan expression. This non-destructive 3D in situ approach revealed the aortic wall microstructure development. Coupling this approach with the intrinsic optical properties of the macromolecules may provide unique vascular wall 3D structure in many pathological conditions, including aortic atherosclerosis, dissections and aneurysms.